Accounting Information Systems’ Effectiveness at Village Credit Institutions (LPDs) in Denpasar City and the Influencing Factors - Ida Ayu, Ratih Manuari; Andre Silvester, Laoh; Ni Made, Karisma Indiani; Ni Putu, Tiara Maharani Krisna Putri (AIBPM Publisher, 2024)
Companies have been forced to adopt computer-based information systems due to the quick development of information technology. These systems expedite and simplify the management's access to data. The purpose of this study is to investigate how the efficiency of Accounting Information Systems (AIS) at Village Credit Institutions (LPDs) in Denpasar City is impacted by factors such as job experience, educational attainment, training, incentives, and task complexity. The population of the study includes 34 LPDs, with a sample of 136 respondents selected through purposive sampling. Multiple linear regression analysis was involved in the data analysis. The findings indicate that while task complexity has a negative influence on AIS' efficacy, job experience and training have a beneficial impact. However, education level and incentives do not significantly influence the system's effectiveness. These findings suggest that LPD managers should prioritize enhancing work experience and training to improve the effectiveness of their AIS.